A personagem feminina no vídeo publicitário “Coco Mademoiselle: the film - Chanel” - Fontana, Vitória (My University, 2019)
This research presents the construction of the female character in the advertising video ?Coco Mademoiselle: The Film?. The research aims to understand the influences of the historical context on the female character construction made in advertising material, related to beauty, fashion, advertising and cinema. Thus, it is necessary to understand the relationships that the concept of the Chanel brand has with the context that was created and how it was developed to this day, when it is noticed that the advertising video in question has a very strong female figure and independent, as well as the fatal woman of cinema noir, but which today, according to the historical context, is built with different objectives according to the contemporary world (sic).
Essa pesquisa apresenta a construção da personagem feminina no vídeo publicitário "Coco Mademoiselle: The Film". A pesquisa tem como objetivo geral compreender as influências do contexto histórico sobre a construção da personagem feita no material publicitário, relacionado com beleza, moda, publicidade e cinema. Dessa forma, se faz necessário entender as relações que o conceito da marca Chanel tem com o contexto que foi criado e como ele foi desenvolvido até os dias de hoje, quando percebe-se que o vídeo publicitário em questão apresenta uma figura feminina muito forte e independente, assim como a mulher fatal do cinema Noir, mas que hoje, segundo o contexto histórico, é construída com diferentes objetivos de acordo com o mundo contemporâneo (sic).
Keywords: Publicidade; Cinema; Personagens e características; Personagens cinematográficos; Mulheres; Filmes publicitários para televisão